The transition path from female workers to neotenic reproductives in the termite Reticulitermes labralis. Issue 4 (4th September 2017) - Su, Xiaohong; Yang, Xiaojuan; Li, Jing; Xing, Lianxi; Liu, He; Chen, Jiaoling
Abstract : Termite workers are characterized by unique flexibility in that a worker can develop in one of three ways: remain a worker, become a soldier within two successive moults, or become a neotenic reproductive (NR) within a single moult. However, is it true that workers can transform into NRs within a single moult? Actually, the developmental pathways of workers turning into NRs remains unclear. In this study, we show for the first time that the female workers of Reticulitermes labralis develop into NRs after a pre‐NRs stage. We found that a female worker became a NR after two successive moults, whereas the male workers copulated directly with queens without undergoing any moults. After the first moult led the female workers into the pre‐NR stage, the length of their abdomens, seventh sternites and ovaries significantly increased. After the second moult from the pre‐NRs stage into NRs, the follicle cells returned to normal, and a few oocytes and follicle cells underwent apoptosis. These results demonstrated that the female pre‐NR type was a transitional type during the development of female workers to the NR caste, and the starting point for oogenesis resumption was the NR stage. We confirmed there were fundamental differences in the reproductive pathway of the male and female workers. Therefore, we determined that the transformation process of the female NRs from workers may be a very complex process, and the reproductive biology of the workers has great potential to provide important and spectacular insights into the evolution strategy of termites.